Recitation of Qur’anic Verses in the Rice Farming Cycle in Pekauman Village East Martapura District - Muhammad Ihsan; Bashori Bashori; Muhammad Araby (PT. Global Pustaka Ilmiah, 2026)
This study was motivated by the tradition of the Pekauman Village community in East Martapura, which practices reading verses from the Qur'an at every stage of the rice farming cycle as a form of spiritual and social endeavor. This study aims to explain religious leaders' understanding of this practice, reveal farmers' motivations for reciting the verses, and analyze its relevance to the agrarian life of the community. Using qualitative methods with a transcendental phenomenological approach, structural functionalism, and social action theory, data were obtained through observation, in-depth interviews, and documentation. The findings show that religious leaders interpret the recitation of the Qur'an as an acknowledgment of Allah's will in the agricultural process and as an ethical-spiritual guideline in their work. Farmers' motivations include spiritual encouragement, psychological calm, hopes for a good harvest, and the strengthening of social solidarity. This practice also functions as a mechanism for adapting to natural uncertainties and reinforcing the collective values of the community. This study concludes that the recitation of Qur'anic verses in the rice farming cycle is not merely a tradition, but a form of living Qur'an that integrates religious, cultural, and economic dimensions. The implication emphasizes the importance of preserving local wisdom and strengthening contextual religious understanding in agrarian communities.